Study of Water Absorption in Raffia vinifera Fibres from Bandjoun, Cameroon - N. R. Sikame Tagne; E. Njeugna; M. Fogue; J.-Y. Drean; A. Nzeukou; D. Fokwa (The Scientific World Journal)
The study is focused on the water diffusion phenomenon through the Raffia vinifera fibre from the stem. The knowledge on the behavior of those fibres in presence of liquid during the realization of biocomposite, is necessary. The parameters like percentage of water gain at the point of saturation, modelling of the kinetic of water absorption, and the effective diffusion coefficient were the main objectives. Along a stem of raffia, twelve zones of sampling were defined. From Fick’s 2nd law of diffusion, a new model was proposed and evaluated compared to four other models at a constant temperature of 23°C. From the proposed model, the effective diffusion coefficient was deduced. The percentage of water gain was in the range of 303–662%. The proposed model fitted better to the experimental data. The estimated diffusion coefficient was evaluated during the initial phase and at the final phase. In any cross section located along the stem of Raffia vinifera, it was found that the effective diffusion coefficient increases from the periphery to the centre during the initial and final phases.